Assorted hyperbolic and trigonometric function solutions of fractional equations with conformable derivative in shallow water - Cevikel, Adem C.; Bekir, Ahmet (WORLD SCIENTIFIC PUBL CO PTE LTD, 2023)
We present the modified simple equation method for solving nonlinear fractional-order partial differential equations (fPDEs). With the presented method, some important fPDEs are solved. We used conformable derivatives to solve these equations. The solutions obtained are both hyperbolic and trigonometric function solutions. Most of these solutions are new solutions not found in the literature.
Keywords: Modified simple equation method; exact solutions; fractional differential equations; conformable derivative; SOLITON-SOLUTIONS; Physics